Ship's response to low-sulfur regulations: From the perspective of route, speed and refueling strategy. (May 2021) - Ma, Dongfang; Ma, Weihao; Hao, Shunfeng; Jin, Sheng; Qu, Fengzhong
Highlights: We propose a method for speed, route and fueling strategy simultaneous planning. This method is suitable for emission control area and wastewater control area. The proposed nonlinear mixed integer programming was solved by transforming into a nonlinear continuous programming model. Impact of fuel prices on speed, routes and fueling strategies is analyzed. Abstract: Optimizing speed, routing, and refueling strategy are three ways to reduce ship operating costs without modifying on ship. Most past studies have simultaneously optimized one or two variables, resulting in a local optimal solution. To limit sulfur emissions, some governments have established Emission Control Areas (ECAs) in recent years, where ships must use low sulphur fuels. The constraints created by ECAs makes the simultaneous optimization of the three variables even more challenging. This study developed a nonlinear mixed integer programming model to address the challenge of simultaneously optimizing the three variables. After transforming the nonlinear discrete mixed integer programming model into a convex nonlinear continuous programming model, the study proposed a solution algorithm for the proposed model. The new model in this study was applied to the Europe-United States (US) and Southeast Asia service route. The results show that the optimal refueling policy, route, and speed selection can be determined simultaneously using the proposed model and solution method. The study investigated the impact of fuel price on ship refueling strategy, route, and speed; and developed insights from the example analyses.